Plant anatomy - Fahn, Abraham, 1916-2012 (Pergamon Press, 1990)
Basic text with an emphasis on functional interpretation of anatomical features. This edition covers structure and development of tissues and cells, ecological anatomy, cambial activity, and new technologies and instrumentation for measuring. The successor to Esau's Plant Anatomy.